HUBUNGAN PENELITIAN SEBAGAI DASAR PENGEMBANGAN ILMU PENGETAHUAN DAN PENGAMBILAN KEPUTUSAN - Supriadi Supriadi; Hendri Yusmanto; Muh Zazin; Mair Mair; Sobirin Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Research relationships play an important role in the development of science and evidence-based decision making. In scientific studies, the relationship between variables becomes the main foundation for understanding phenomena systematically and logically. This study aims to analyze the role of research relationships in supporting scientific development and decision making in various fields. The method used in this study is a qualitative approach with a library research method through the study of books, journals, and relevant scientific literature. The results of the study indicate that research relationships, both causal, correlational, and descriptive, contribute significantly to building scientific concepts, strengthening theories, and producing accurate information for decision making. In addition, understanding research relationships also supports the preparation of more systematic research methodologies and improves the validity of scientific findings. Therefore, research relationships become an important element in the advancement of science and in determining policies and solutions based on scientific data.